Pancreas Cancer‐Associated Weight Loss. (27th December 2018) - Hendifar, Andrew E.; Petzel, Maria Q.B.; Zimmers, Teresa A.; Denlinger, Crystal S.; Matrisian, Lynn M.; Picozzi, Vincent J.; Rahib, Lola; ,
Abstract: : Unintentional weight loss in patients with pancreatic cancer is highly prevalent and contributes to low therapeutic tolerance, reduced quality of life, and overall mortality. Weight loss in pancreatic cancer can be due to anorexia, malabsorption, and/or cachexia. Proper supportive care can stabilize or reverse weight loss in patients and improve outcomes. We review the literature on supportive care relevant to pancreatic cancer patients, and offer evidence‐based recommendations that include expert nutritional assessment, counseling, supportive measures to ensure adequate caloric intake, pancreatic enzyme supplementation, nutritional supplement replacement, orexigenic agents, and exercise. Pancreatic Cancer Action Network‐supported initiatives will spearhead the dissemination and adoption of these best supportive care practices. Abstract : This review highlights the etiology, assessment, and management of unintentional weight loss in patients with pancreatic cancer and provides recommendations for best supportive care.